Recent advances of the role of Prrx1 in bone development and bone remodeling - FENG Xi; WANG Zuolin (Kouqiang hemian waike zazhi)
As a marker of mesenchymal cells, the transcription factor paired related homeobox 1 (Prrx1) not only participates in the bone development process during the embryonic period, but also plays a role in the adjustment of the body's bone homeostasis and the repair process after injury in adulthood. Prrx1+ cells are a subpopulation of the body's mesenchymal cells, which are believed to be involved in the development and formation of long bones and skulls as osteogenic precursor cells. This article reviews the role and influence of Prrx1 and Prrx1+ cells in bone development and bone remodeling.